2014
DOI: 10.1186/1471-2296-15-132
|View full text |Cite
|
Sign up to set email alerts
|

Implementing cardiometabolic health checks in general practice: a qualitative process evaluation

Abstract: BackgroundA stepwise screening approach for the detection and management of cardiometabolic disease is proposed in various primary care guidelines. The aim of this study was to explore the implementation of a cardiometabolic health check as perceived by the involved caregivers and patients.MethodsQualitative process evaluation of the implementation of a cardiometabolic screening programme in a multidisciplinary primary healthcare centre in Eindhoven, the Netherlands, in which 1270 patients had participated. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This is in agreement with previous findings 14 . A previous study showed that GPs were enthusiastic about offering health checks for CMD, and that they preferred systematic screening to case-finding 15 . This indicates that motivated GPs can play a key role in selective prevention programmes.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous findings 14 . A previous study showed that GPs were enthusiastic about offering health checks for CMD, and that they preferred systematic screening to case-finding 15 . This indicates that motivated GPs can play a key role in selective prevention programmes.…”
Section: Discussionsupporting
confidence: 92%
“… 22 , 23 Previous research has identified the importance of HCPs interpreting and communicating results and information on risk, clearly and to ensure that it is personalized. 6 , 24 , 25 Previous findings also reported that some patients sometimes found their QRisk2 score confusing and that it held no meaning or significance to them. 6 , 16 , 26 There are potential limitations in relying on risk score as a trigger for facilitating behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…21 There are conflicting findings on the impact of attending preventative programmes. 21 , 22 , 25 Some studies report that patients sometimes experience anxiety and stress associated with the receipt of negative or high-risk results 21 , 25 whilst others found no associated harms from attending CVD checks. 22 …”
Section: Discussionmentioning
confidence: 99%
“…With this approach, we have tackled some earlier identified challenges such as good preparation of involved staff and the integration of the program within everyday practice. 21 Another strength was that we were able to collect the EHR data of 97% of the patients, instead of the anticipated 90%. 15 The small number of missing data (3%) was equally distributed among patients of different risk categories and therefore we assume these data were missing at random and did not influence our results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%